2016
DOI: 10.1039/c6nr00562d
|View full text |Cite
|
Sign up to set email alerts
|

Nacre-inspired integrated strong and tough reduced graphene oxide–poly(acrylic acid) nanocomposites

Abstract: Inspired by the relationship between interface interactions and the high performance mechanical properties of nacre, a strong and tough nacre-inspired nanocomposite was demonstrated based on graphene oxide (GO) and polyacrylic acid (PAA) prepared via a vacuum-assisted filtration self-assembly process. The abundant hydrogen bonding between GO and PAA results in both high strength and toughness of the bioinspired nanocomposites, which are 2 and 3.3 times higher than that of pure reduced GO film, respectively. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 29 publications
2
78
0
Order By: Relevance
“…[51,58,90] Figure 2 shows that in the past decade, an increasing research effort has been made to improve the mechanical properties of graphene-based nanocomposites by various interfacial www.advmatinterfaces.de modifications. [48,75,[91][92][93][94] The interfacial crosslinking strategies contain hydrogen bonding, [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] ionic bonding, [81,[115][116][117][118] π-π interaction, [119][120][121] and covalent bonding. Inspired by nacre, a vast variety of highperformance GO-based nanocomposites and their reduced counterparts, including 1D fibers, 2D films, and 3D bulk materials, have been successfully constructed by interfacial crosslinking and building block toughening.…”
Section: Interfacial Architecture Of Biological Materialsmentioning
confidence: 99%
“…[51,58,90] Figure 2 shows that in the past decade, an increasing research effort has been made to improve the mechanical properties of graphene-based nanocomposites by various interfacial www.advmatinterfaces.de modifications. [48,75,[91][92][93][94] The interfacial crosslinking strategies contain hydrogen bonding, [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] ionic bonding, [81,[115][116][117][118] π-π interaction, [119][120][121] and covalent bonding. Inspired by nacre, a vast variety of highperformance GO-based nanocomposites and their reduced counterparts, including 1D fibers, 2D films, and 3D bulk materials, have been successfully constructed by interfacial crosslinking and building block toughening.…”
Section: Interfacial Architecture Of Biological Materialsmentioning
confidence: 99%
“…GO nanosheets are an ideal candidate for fabrication of nacre-like film nanocomposites via hydrogen bonding. [71][72][73][74] Li et al [73] reported a GO-polyvinyl alcohol (PVA) film nanocomposite fabricated by evaporation. After HI reduction, the Figure 6.…”
Section: Extension Of Bioinspired Fabricationmentioning
confidence: 99%
“…[87][88][89][90][91][92][93][94][95][96] Vacuum filtration was used to rapidly self-assemble GO/gellan gum into aligned nacre-like films. The produced films were strong and flexible.…”
Section: Gellan Gum Filmsmentioning
confidence: 99%
“…The favorable properties of these polymers include good biocompatibility, biodegradability, and ease of handling. [116][117][118] Some other very rarely studied synthetic polymers for potential biomedical sciences are poly(carbonate urethane), [119] poly(acrylic acid), [92] poly(l-lysine), [120] and elastomers. [121][122][123] 2.2.1.…”
Section: Synthetic Polymersmentioning
confidence: 99%